2022
DOI: 10.2217/cer-2022-0088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of noninvasive prenatal screening for defined pathogenic microdeletion/microduplication syndromes and nonsyndromic copy number variations: a large multicenter study

Abstract: Background: This retrospective study assessed the precision of noninvasive prenatal testing (NIPT) in detecting microdeletion/microduplication syndromes (MMSs) and nonsyndromic copy number variations (CNVs). Methods: The study included 19,086 singleton pregnancies screened on NIPT using high-throughput sequencing. Pregnancies with CNVs on NIPT underwent amniocentesis for karyotyping and CNV sequencing (CNV-seq). We analyzed pathogenic MMSs and nonsyndromic CNVs separately, dividing the CNVs into subgroups base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…In total, 7845 search results were identified, of which 1862 were duplicates. After screening the remaining 5983 results, 63 articles satisfied the inclusion criteria 12,14–16,18,26–83 . The study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 7845 search results were identified, of which 1862 were duplicates. After screening the remaining 5983 results, 63 articles satisfied the inclusion criteria 12,14–16,18,26–83 . The study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 63 included studies, PPV results were calculated from 59 (48 case‐series, 12,14–16,18,26–28,30,33–38,40–46,48,49,52–59,61–66,68–71,74,78–82 and 11 cohort studies 29,47,50,60,67,72,73,75–77,83 ). Sensitivity and specificity were reported from nine (four case‐controls, 31,32,39,51 five cohort studies with complete diagnostic confirmation 29,60,75–77 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall screen-positive rate for CNVs, regardless of size or pathogenicity, ranges from 0.1% to 0.9%, with reported sensitivities of 20% to 100% 11,[13][14][15][16][17][18][19][20][22][23][24][25]38,40,[53][54][55][56][57][58][59] .…”
Section: Cfdna For Copy Number Variantsmentioning
confidence: 99%
“…Some studies report a true positive when the fetus is demonstrated by diagnostic genetic testing to harbor the CNV in question, whereas others consider the detection of the genetic anomaly in placental, maternal, or fetal tissues as a true positive 15,62,63 . Unfortunately, VUS and nonsyndromic CNVs were excluded from the calculation of PPVs in some trials but not in others 55 . In one report, VUS/benign CNVs accounted for ~19% of those confirmed to be fetal in origin 23 .…”
Section: Cfdna For Copy Number Variantsmentioning
confidence: 99%